The role of institutional quality on the performance in the export of coconut products - Jessie Lin; Insa Flachsbarth; Stephan von Cramon-Taubadel (Agricultural Economics, 2020)
The literature that addresses the role of institutions in bilateral trade is extensive. However, research that links institutional quality to specific products and their different levels of value addition is lacking. In this study, we look into institutional quality, based on three indicators from the World Bank's world governance indicators, and its indicator-specific effects on bilateral coconut trade. In particular, we study coconut products with varying degrees of value addition. We use structural gravity models to measure how institutions affect the trade performance of the top 26 coconut producing countries to the top 15 importing economies over the years 1996–2016. Our results suggest that increased government effectiveness enhances trade of high-value products, whereas better voice and accountability scores decrease trade of coconut products with both levels of value addition. No clear trade effect is observed when two countries are more similar in each of the three indicators. We conclude that each indicator has different trade effects on each of the coconut product categories. We end by giving recommendations that will help to improve the coconut export performance in their respective countries and for future research.
Keywords: 330; coconut trade; gravity model; institutional quality; value-added; F14; Q17; Q18; P48